2010
DOI: 10.1111/j.1439-0396.2009.00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding liquiddl‐methionine hydroxy analogue‐free acid to drinking water on growth performance and small intestinal morphology of nursery pigs

Abstract: This study was conducted to evaluate the effect of adding liquid DL-methionine hydroxy analogue free acid (LMA) to drinking water on growth performance, small intestinal morphology and volatile fatty acids in the caecum of nursery pigs. Twenty-four crossbred pigs (Large White x Landrace, BW approximately 18 kg) were divided into three groups with four replications of two piglets each. The piglets received drinking water without (control), with 0.05 or 0.10% LMA. The results indicated that adding LMA at 0.10% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…As expected, our study found that the villus-to-crypt ratio of small intestine were linearly improved by increasing dietary SID SAA:Lys. These findings are in agreement with the previous studies (Bauchart-Thevret et al 2009;Kaewtapee et al 2010;Kahindi 2014), they suggested that the improvement of small intestinal morphology as a result of increasing SAA or Met content in pigs diets. Therefore, it can be concluded that dietary SAA content promoted intestinal growth and abundant SAA could enhance enterocytes production by the crypt leading to longer villi.…”
Section: Discussionsupporting
confidence: 83%
“…As expected, our study found that the villus-to-crypt ratio of small intestine were linearly improved by increasing dietary SID SAA:Lys. These findings are in agreement with the previous studies (Bauchart-Thevret et al 2009;Kaewtapee et al 2010;Kahindi 2014), they suggested that the improvement of small intestinal morphology as a result of increasing SAA or Met content in pigs diets. Therefore, it can be concluded that dietary SAA content promoted intestinal growth and abundant SAA could enhance enterocytes production by the crypt leading to longer villi.…”
Section: Discussionsupporting
confidence: 83%
“…The measurements of villus height and crypt depth were performed on stained sections under the microscope with an ocular micrometer and 40× combined magnification. Villus height was measured from the villus tip to the villus‐crypt junction, whereas crypt depth was measured from this junction to the base of the crypt (Kaewtapee et al ; Walsh et al ; Shen et al ). At least 10 well‐oriented and intact villi and their associated crypts were measured in each slide.…”
Section: Methodsmentioning
confidence: 99%
“…The microbial enumerations of cecum aerobes, Escherichia coli , Lactobacillus and Bifidobacteria , were determined using plate culture (Kaewtapee et al ). Cecal digesta were serially diluted with sterile physiological saline according to the procedure described by Engberg et al ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the property of organic acids, Kaewtapee et al (2010) reported that adding LMA in drinking water reduced the total plate count and Escherichia coli (E. coli) in the water and consequently improved growth performance of piglets. In poultry, Poosuwan et al (2007) demonstrated that the minimum inhibitory concentration (MIC) of LMA for E. coli was 0.24% v/v in water, and this level promoted growth performance and tended to reduce E. coli in the gastrointestinal tract of broiler chicks.…”
Section: Introductionmentioning
confidence: 99%